Review of the Common Deposition Methods of Thin-Film Pentacene, Its Derivatives, and Their Performance - Yunus Y.; Mahadzir N.A.; Ansari M.N.M.; Aziz T.H.T.A.; Afdzaluddin A.M.; Anwar H.; Wang M.; Ismail A.G. (MDPI, 2023)
Coatings; Deposition rates; Fabrication; Field effect transistors; Flexible electronics; Industrial research; Ink jet printing; Organic light emitting diodes (OLED); Thin film circuits; Thin film transistors; Thin films; Vacuum evaporation; Deposition methods; Ink-jet printing; Large-scales; Organic thin film transistors; Pentacenes; Performance; Solution process; Thermal-vacuum evaporation; Thin-film depositions; Thin-films; Thermal evaporation